Practicing the way : be with Jesus, become like Him, do as He did - Comer, John Mark, 1980- (WaterBrook, 2024)
"The New York Times bestselling author of The Ruthless Elimination of Hurry and Live No Lies reveals the obstacles holding us back from authentically following Jesus and presents countercultural practices to connect us with a vibrant, lifelong faith"--